Government Policy in the Provision of Sports Facilities in Kudus Regency (Evaluation Study in the Provision of Sports Facilities and Infrastructure in Kudus Regency) - Sugiyarto, Totok; Nasuka, Nasuka; Wahyudi, Agung (Journal of Physical Education and Sports, 2021)
The government of Kudus Regency plays a central role to determine a policy in the provision of sports facilities (Sport Centre) to meet the lack of infrastructure and to support the achievements of the sports in Kudus. This study employed a qualitative approach with the CIPP (Context, Input, Process, and Product) evaluation model. The subjects of this study were the Regional Government of Kudus Regency, the Education, Youth, and Sports Service of Kudus Regency, the Chairperson of KONI, Trainers, and Sports Instructors. They were chosen to produce a reliable or trustworthy picture of the government policy in the provision of sports facilities in Kudus Regency. The data were collected through observations, interviews, and documentation. Data triangulation was applied as a technique to analyze the data. It consists of data collection, data reduction, data presentation, and drawing conclusions. Research Findings 1) Context Evaluation, the aim of the Policy and Development Priorities to meet the lack of infrastructure, to support sports achievement, and to build public facilities is mainly for sports achievements, educational sports, and recreational sports, 2) Input Evaluation, the policy must be research-based and future-oriented with the principle of achieving the goals to increase achievements and sports culture as well as to increase the Original Local Government Revenue, 3) Process Evaluation, the implementation of the development is carried out through stages and mechanisms guided by priority scale based on the list of budget usage of each year, 4) Product Evaluation, standardization of the venues which are built following the national standards. The position of the policy-makers is as the person in charge of overall activities starting from planning to supervision and the authority program organizer of the Education, Youth, and Sports Service is as the manager The government of Kudus Regency plays a central role to determine a policy in the provision of sports facilities (Sport Centre) to meet the lack of infrastructure and to support the achievements of the sports in Kudus. This study employed a qualitative approach with the CIPP (Context, Input, Process, and Product) evaluation model. The subjects of this study were the Regional Government of Kudus Regency, the Education, Youth, and Sports Service of Kudus Regency, the Chairperson of KONI, Trainers, and Sports Instructors. They were chosen to produce a reliable or trustworthy picture of the government policy in the provision of sports facilities in Kudus Regency. The data were collected through observations, interviews, and documentation. Data triangulation was applied as a technique to analyze the data. It consists of data collection, data reduction, data presentation, and drawing conclusions. Research Findings 1) Context Evaluation, the aim of the Policy and Development Priorities to meet the lack of infrastructure, to support sports achievement, and to build public facilities is mainly for sports achievements, educational sports, and recreational sports, 2) Input Evaluation, the policy must be research-based and future-oriented with the principle of achieving the goals to increase achievements and sports culture as well as to increase the Original Local Government Revenue, 3) Process Evaluation, the implementation of the development is carried out through stages and mechanisms guided by priority scale based on the list of budget usage of each year, 4) Product Evaluation, standardization of the venues which are built following the national standards. The position of the policy-makers is as the person in charge of overall activities starting from planning to supervision and the authority program organizer of the Education, Youth, and Sports Service is as the manager.